Mental Imagery to Reduce Alcohol-related harm in patients with alcohol dependence and alcohol-related liver damaGE: the MIRAGE pilot trial protocol. Issue 5 (18th May 2022) - Dhanda, Ashwin D; Allende, Hannah; Allgar, Victoria; Andrade, Jackie; Bailey, Matthew Peter; Callaghan, Lynne; Cocking, Laura; Goodwin, Elizabeth; Hawton, Annie; Hayward, Christopher; Hudson, Ben; Jeffery, Alison; et al.
Abstract : Introduction: In the UK, alcohol use is the main driver of chronic liver disease and each year results in over 1 million unplanned hospital admissions and over 25 000 deaths from alcohol-related liver disease (ArLD). The only effective treatment to prevent progression of liver damage is reducing or ceasing alcohol consumption. Psychological and pharmacological therapies for alcohol misuse are ineffective in patients with ArLD. Functional imagery training (FIT) is a novel psychological therapy that builds on motivational interviewing techniques with multisensory imagery. This pilot trial aims to test the feasibility of training alcohol liaison nurses to deliver FIT therapy and of recruiting and retaining patients with ArLD and alcohol dependence to a randomised trial of FIT and treatment as usual (TAU) versus TAU alone. Methods and analysis: This is a randomised pilot trial of FIT and TAU versus TAU alone in 90 patients with ArLD and alcohol dependence admitted to one of four UK centres. The primary objectives are to estimate rates of screening, recruitment, randomisation, retention, adherence to FIT/TAU and a preliminary assessment of the FIT intervention in the ArLD population. Data from the pilot study will be used to finalise the design of a definitive randomised controlled trial to assess the effectiveness and cost-effectiveness of FIT. The proposed primary outcome measure for the definitive trial is self-reported alcohol use assessed using timeline follow-back. Ethics and dissemination: Research ethics approval was given by the Yorkshire and Humber–Bradford Leeds Research Ethics Committee (reference: 21/YH/0044). Eligible patients will be approached and written informed consent obtained prior to participation. Results will be disseminated through peer-reviewed open access journals, international conferences and a lay summary published on the Trials Unit website and made available to patient groups. Trial registration number: ISRCTN41353774 .